Measurement of the relative branching fraction of upsilon(4S) to charged and neutral B-meson pairs. - Alexander, J; Baker, R; Bebek, C; Berger, B; Berkelman, K; Blanc, F; Boisvert, V; Cassel, D; Dickson, M; Drell, P; Ecklund, K; Ehrlich, R; et al. (2001)
We analyze 9.7x10(6) B_B pairs recorded with the CLEO detector to determine the production ratio of charged to neutral B-meson pairs produced at the Upsilon(4S) resonance. We measure the rates for B0-->J/psiK((*)0) and B+-->J/psiK((*)+) decays and use the world-average B-meson lifetime ratio to extract the relative widths f(+-) / f(00) = gamma(Upsilon(4S)-->B+B-) / gamma(Upsilon(4S)-->B0 B-0)) = 1.04+/-0.07(stat)+/-0.04(syst). With the assumption that f(+-)+f(00) = 1, we obtain f(00) = 0.49+/-0.02(stat)+/-0.01(syst) and f(+-) = 0.51+/-0.02(stat)+/-0.01(syst). This production ratio and its uncertainty apply to all exclusive B-meson branching fractions measured at the Upsilon(4S) resonance.